O pixo como ato político - Cunha, Marcelo Perini Peralta (2019)
The present work focuses on analyzing picho as a form of urban intervention distinct from others such as graffiti and street art. We first approach this separation between graffiti and picho that occurs only in Brazil. We analyze how they are activities that have a paradoxical relationship where graffiti is accepted as a legitimate work of art and transformed into another cultural commodity of the cities, as well as a way of acting in the urban environment to promote its valorization, while picho refuses to follow this line and remain deliberately illegal, constantly questioning the public character of our cities and their strategic marketing management. By doing so, it is an undeniably political act of contesting the way cities are managed today and how they can be appropriated by their citizens.